Loss of tumor-derived SMAD4 enhances primary tumor growth but not metastasis following BMP4 signalling - Lap Hing Chi; Andrew D. Redfern; Suraya Roslan; Ian P. Street; Allan D. Burrows; Robin L. Anderson (Cell Communication and Signaling, 2024)
Abstract Background Bone morphogenetic protein 4 (BMP4) is a potent inhibitor of breast cancer metastasis. However, a tumor-promoting effect of BMP4 is reported in other tumor types, especially when SMAD4 is inactive. Methods To assess the requirement for SMAD4 in BMP4-mediated suppression of metastasis, we knocked down SMAD4 in two different breast tumors and enforced SMAD4 expression in a third line with endogenous SMAD4 deletion. In addition, we assessed the requirement for SMAD4 in tumor cell-specific BMP signalling by expression of a constitutively active BMP receptor. Delineation of genes regulated by BMP4 in the presence or absence of SMAD4 was assessed by RNA sequencing and a BMP4-induced gene, MYO1F was assessed for its role in metastasis. Genes regulated by BMP4 and/or SMAD4 were assessed in a publicly available database of gene expression profiles of breast cancer patients. Results In the absence of SMAD4, BMP4 promotes primary tumor growth that is accompanied by increased expression of genes associated with DNA replication, cell cycle, and MYC signalling pathways. Despite increased primary tumor growth, BMP4 suppresses metastasis in the absence of tumor cell expression of SMAD4. Consistent with the anti-metastatic activity of BMP4, enforced signalling through the constitutively active receptor in SMAD4 positive tumors that lacked BMP4 expression still suppressed metastasis, but in the absence of SMAD4, the suppression of metastasis was largely prevented. Thus BMP4 is required for suppression of metastasis regardless of tumor SMAD4 status. The BMP4 upregulated gene, MYO1F, was shown to be a potent suppressor of breast cancer metastasis. Gene signature upregulated by BMP4 in the absence of SMAD4 was associated with poor prognosis in breast cancer patients, whereas gene signature upregulated by BMP4 in the presence of SMAD4 was associated with improved prognosis. Conclusions BMP4 expression is required for suppression of metastasis regardless of the SMAD4 status of the tumor cells. Since BMP4 is a secreted protein, we conclude that it can act both in an autocrine manner in SMAD4-expressing tumor cells and in a paracrine manner on stromal cells to suppress metastasis. Deletion of SMAD4 from tumor cells does not prevent BMP4 from suppressing metastasis via a paracrine mechanism.